Ultra-precision machining of electroless-nickel for very long cutting distance - Pramanik, Alokesh; Rahman, M. (LAP Lambert Academic Publishing, 2012)
Study on ultra-precision machining, where diamond cutting tools are used to achieve submicron tolerance and a nano-meter surface finish, has increased since the 1960s. Surfaces of the popular metals (copper and aluminium) machined by diamond tools are ruined easily by abrasion and corrosion. An attractive metal in these fields is nickel-phosphorus alloy. This material is hard, corrosion resistant and its properties can be customised by changing phosphorus content. This book focuses on the optimization of machining parameters and phosphorus content of electroless-nickel during ultra-precision machining of this material. In addition, this book presents the effects of origin of diamond tool, phosphorus content, depth of cut, crystal orientation of cutting edge and rake angle on surface finish, tool wear and cutting forces for a very long cutting distance (202.8 km). It is found that higher feedrate gives worse surface finish and higher cutting forces, however the surface finish becomes better and cutting forces decrease with the increase of phosphorus content during ultra-precision machining of electroless-nickel. The depth-of-cut does not have any significant effect on surface roughness but cutting forces increase with the increase of depth-of-cut. Cutting forces increase slightly with the increase of spindle speed and there is a critical value of spindle speed for the best surface finish. Natural diamond tools perform better than that of artificial diamond in terms of wear, surface finish and forces, although the cost of natural diamond tool is three to four times higher than that of artificial diamond tool.Severe tool wear is observed for machining lower phosphorus contents electroless-nickel, but tool wear is negligible for higher phosphorus contents electroless-nickel. The lower depth-of-cut gives higher tool wear although the performances in other areas are similar to higher depth-of-cut. Crystal orientation {110} shows better performance over the tool with {100} crystal orientation at rake face. Machining with tools of rake angles 0º and -15º showed better (stable) surface finish and lower tool wear compared to that of -5º rake angle.